Modular protein-protein interactions provide a general mechanism to organize dynamic cellular systems - Pawson, Tony (Henry Stewart Talks, 2010)
Mechanisms through which protein interactions modules, such as the SH2 domain, mediate the activation of specific signaling pathways by normal and oncogenic tyrosine kinases, The biological functions and biochemical properties of interaction domains including their roles in controlling protein localization, in recognition of post-translational modifications, in forming multi-protein complexes, and in regulating enzymatic function, The versatility of interaction domains, their potential utility in the evolution of new signaling pathways, and their exploitation by pathogenic proteins to rewire cellular behavior
Archived at 2018/05/31